190k views
0 votes
f(x) = 4x² + 5x – 3g(x) = 4x³ – 3x² + 5Find (f - g)(x).A. (f - g)(x) = 4x³ + x² + 5x + 2B. (f - g)(x) = 4x³ – 7x² – 5x + 8C. (f - g)(x) = -4x³ + x² + 5x + 2D. (f - g)(x) = -4x³ + 7x² + 5x – 8

User Skamradt
by
4.9k points

1 Answer

3 votes

Given the following functions:

f(x) = 4x² + 5x – 3

g(x) = 4x³ – 3x² + 5

Finding (f-g)(x) means f(x) - g(x).

We get,


\text{ (f-g)(x) = f(x) - g(x)}
\text{f(x) - g(x) = (}4x^(2)+5x-3)\text{ - (}4x^(3)-3x^(2)+5)
\text{= }4x^2+5x-3\text{-}4x^3+3x^2-5
\text{= -}4x^3+4x^2+3x^2+5x-3-5
\text{= -}4x^3+7x^2+5x-8

Therefore, the answer is letter D. (f - g)(x) = -4x³ + 7x² + 5x – 8

User Barry Pitman
by
5.2k points